2011
DOI: 10.4007/annals.2011.174.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Hilbert modular forms and the Gross-Stark conjecture

Abstract: Let F be a totally real field and χ an abelian totally odd character of F . In 1988, Gross stated a p-adic analogue of Stark's conjecture that relates the value of the derivative of the p-adic L-function associated to χ and the p-adic logarithm of a p-unit in the extension of F cut out by χ. In this paper we prove Gross's conjecture when F is a real quadratic field and χ is a narrow ring class character. The main result also applies to general totally real fields for which Leopoldt's conjecture holds, assuming… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
107
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(109 citation statements)
references
References 17 publications
2
107
0
Order By: Relevance
“…Theorem 1 above holds unconditionally and concerns the p-adic logarithms of the same -units, for primes p = . It therefore bears no direct connection with the Gross-Stark conjecture, even though its proof, like that of the Gross-Stark conjecture given in [9] and [18], relies crucially on the deformation theory of p-adic Galois representations.…”
Section: Remark 15mentioning
confidence: 95%
“…Theorem 1 above holds unconditionally and concerns the p-adic logarithms of the same -units, for primes p = . It therefore bears no direct connection with the Gross-Stark conjecture, even though its proof, like that of the Gross-Stark conjecture given in [9] and [18], relies crucially on the deformation theory of p-adic Galois representations.…”
Section: Remark 15mentioning
confidence: 95%
“…In [DDP11,§1], it is shown that dim E H 1 p (F, E(χ −1 )) = 1, and that the unique class (up to a scalar) is ramified at p. In other words, if we write its restriction to p as xκ ur + yκ cyc , then y = 0. In fact we have Proposition 1 (loc.…”
Section: Introductionmentioning
confidence: 99%
“…Kubota-Leopoldt p-adic L-functions Greenberg 1978, 1979;Gross and Koblitz 1979). We also remark that in Dasgupta et al (2011) this result was generalized to totally real fields (assuming the Leopoldt conjecture). We also remark that in Dasgupta et al (2011) this result was generalized to totally real fields (assuming the Leopoldt conjecture).…”
Section: Extra Zerosmentioning
confidence: 64%